A tRNA- and Anticodon-Centric View of the Evolution of Aminoacyl-tRNA Synthetases, tRNAomes, and the Genetic Code - Yunsoo Kim; Kristopher Opron; Zachary F. Burton (Life, 2019)
Pathways of standard genetic code evolution remain conserved and apparent, particularly upon analysis of aminoacyl-tRNA synthetase (aaRS) lineages. Despite having incompatible active site folds, class I and class II aaRS are homologs by sequence. Specifically, structural class IA aaRS enzymes derive from class IIA aaRS enzymes by in-frame extension of the protein N-terminus and by an alternate fold nucleated by the N-terminal extension. The divergence of aaRS enzymes in the class I and class II clades was analyzed using the Phyre2 protein fold recognition server. The class I aaRS radiated from the class IA enzymes, and the class II aaRS radiated from the class IIA enzymes. The radiations of aaRS enzymes bolster the coevolution theory for evolution of the amino acids, tRNAomes, the genetic code, and aaRS enzymes and support a tRNA anticodon-centric perspective. We posit that second- and third-position tRNA anticodon sequence preference (C>(U~G)>A) powerfully selected the sectoring pathway for the code. GlyRS-IIA appears to have been the primordial aaRS from which all aaRS enzymes evolved, and glycine appears to have been the primordial amino acid around which the genetic code evolved.